1993
DOI: 10.1364/ao.32.004557
|View full text |Cite
|
Sign up to set email alerts
|

Coherent launch-site atmospheric wind sounder: theory and experiment

Abstract: The coherent launch-site atmospheric wind sounder (CLAWS) is a lidar atmospheric wind sensor designed to measure the winds above space launch facilities to an altitude of 20 km. In our development studies, lidar sensor requirements are defined, a system to meet those requirements is defined and built, and the concept is evaluated, with recommendations for the most feasible and cost-effective lidar system for use as an input to a guidance and control system for missile or spacecraft launches. The ability of CLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…There are a number of studies on the turbulent fluxes measurement over the sea surface. Various motion sensing techniques on the moving platform have been developed in the field of airborne (Axford, 1968), spaceborne (Hawley et al, 1993), and shipborne observations (Fujitani, 1992;Song et al, 1996;Edson et al, 1998;Miller et al, 2008;Tucker et al, 2009). Many shipborne field experiments have been widely carried out over Pacific Ocean (Mitsuta and Fujitani, 1974;Bradley et al, 1991;Shao, 1995;Tsukamoto et al, 1995;Tucker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies on the turbulent fluxes measurement over the sea surface. Various motion sensing techniques on the moving platform have been developed in the field of airborne (Axford, 1968), spaceborne (Hawley et al, 1993), and shipborne observations (Fujitani, 1992;Song et al, 1996;Edson et al, 1998;Miller et al, 2008;Tucker et al, 2009). Many shipborne field experiments have been widely carried out over Pacific Ocean (Mitsuta and Fujitani, 1974;Bradley et al, 1991;Shao, 1995;Tsukamoto et al, 1995;Tucker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the turbulent fluxes measurement over the sea surface (Axford, 1968;Mitsuta et al, 1974;Bradley et al, 1991;Fujitani, 1992;Hawley et al, 1993;Shao, 1995;Tsukamoto et al, 1995;Song et al, 1996;Edson et al, 1998;Miller et Atmos. Meas.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been put into 2 µm pulsed systems mainly intended for wind measurements [2] [3]. Hawley et al [4] developed a 1.06 µm pulsed CDL system for wind sensing. Karlsson et al [5] reported a 1.5 µm cw all-fiber wind sensing CDL system.…”
Section: Introductionmentioning
confidence: 99%